Efektifitas Integrasi Program Pendidikan Tahfiz, Diniyah, dan Akademik dalam Membentuk Karakter Santri Pondok An-Nahdloh Malaysia - Muhammad Agil Miqdad; Muhammad Mukhlis Arif; Wardah Zairina; Nurul Auliana; Devira Linawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The integration of tahfiz, diniyah education, and academic curriculum is an important approach in the development of modern Islamic boarding schools to produce students who excel spiritually, intellectually, and socially. This study aims to analyze the effectiveness of the integration of tahfiz, diniyah, and academic programs in strengthening the competencies of students at Pondok An-Nahdloh Malaysia. The research uses a descriptive qualitative approach with data collection techniques through participatory observation of daily learning activities and analysis of institutional documents. Data analysis was conducted using Miles and Huberman's interactive model with Robin Fogarty's curriculum integration theoretical framework. The results show that curriculum integration is implemented through the alignment of tahfiz activities, the study of turats books in diniyah education, and formal academic learning in a mutually supportive learning system. This practice reflects a combination of sequenced and integrated models that enable comprehensive material and learning experiences for santri. This integration contributes to improving students' ability to memorize the Qur'an, their understanding of Islamic scholarship, their academic achievement, and the formation of their religious character and social skills.